In Vivo Antitumor Effect against Murine Cells of CT26 Colon Cancer and EL4 Lymphoma by Autologous Whole Tumor Dead Cells. (3rd February 2021) - Barrera-Avalos, Carlos; Díaz, Ximena; Madrid, Bastián; Michelson, Sofía A.; Robles-Planells, Claudia; Sánchez-Guerrero, Giselle; Ahumada, Viviana; Mella-Torres, Andrea; Rojo, Leonel E.; Imarai, Mónica; Milla, Luis A.; Leiva-Salcedo, Elías; et al.
Abstract : Active immunotherapy against cancer is based on immune system stimulation, triggering efficient and long-lasting antigen-specific immune responses. Immunization strategies using whole dead cells from tumor tissue, containing specific antigens inside, have become a promising approach, providing efficient lymphocyte activation through dendritic cells (DCs). In this work, we generate whole dead tumor cells from CT26, E.G7, and EL4 live tumor cells as antigen sources, which termed immunogenic cell bodies (ICBs), generated by a simple and cost-efficient starvation-protocol, in order to determine whether are capable of inducing a transversal anticancer response regardless of the tumor type, in a similar way to what we describe previously with B16 melanoma. We evaluated the anticancer effects of immunization with doses of ICBs in syngeneic murine tumor models. Our results showed that mice's immunization with ICBs-E.G7 and ICBs-CT26 generate 18% and 25% of tumor-free animals, respectively. On the other hand, all carrying tumor-animals and immunized with ICBs, including ICBs-EL4, showed a significant delay in their growth compared to not immunized animals. These effects relate to DCs maturation, cytokine production, increase in CD4+T-bet+ and CD4+ROR- γ t+ population, and decrease of T regulatory lymphocytes in the spleen. Altogether, our data suggest that whole dead tumor cell-based cancer immunotherapy generated by a simple starvation protocol is a promising way to develop complementary, innovative, and affordable antitumor therapies in a broad spectrum of tumors.